ANALISIS PENDAPATAN DAN KONDISI PEMBERDAYAAN PETANI KOPI SISTEM INTEGRASI DENGAN TERNAK KAMBING BINAAN STARBUCK FARMER SUPPORT CENTRE DI KECAMATAN RONGGUR NIHUTA KABUPATEN SAMOSIR - Nainggolan, Hotden Leonardo; Ginting, Albina; Tampubolon, Jongkers; Simanjuntak, Trinitatis Havandi; Situmorang, Echa Yohana (Fakultas Pertanian, Universitas Janabadra, 2024)
This research aims to determine the income of coffee farming and goat farming as well as the conditions for empowering coffee farmers in an integrated system with goat farming. The research was conducted in Sub-district Ronggur Nihuta, Samosir District, which was determined deliberately. The population in this research are farmers who have developed coffee farming in an integrated manner with goat farming and have been fostered by the Starbucks Farmer Support Center for 87 families with a sample size of 30 respondents. This research uses primary data obtained through interviews with respondents and secondary data obtained from official sources such as; from the Samosir Regency Central Statistics Agency, and other sources. The data in the research were analyzed descriptively. Based on the research results it was concluded; a) the average income of an integrated coffee farming system with goat farming is IDR 14,150,186.64; b) the average income of goat farming business with an integrated system with coffee commodities IDR 4,685,738.13; c) The empowerment carried out by the Starbucks Farmer Support Center for coffee farmers with an integrated system with goat farming, plays a very important role in encouraging farmers to follow suit; training, counseling, technical guidance and direction regarding the development of integrated coffee farming and goat farming. Based on the research results it is recommended; a) for farmers to optimize the management of coffee farming with goats in an integrated manner, by increasing farmers' understanding and knowledge through counseling, training, processing plant waste for animal feed and fertilizer; b) so that the Starbucks Farmer Support Center carries out ongoing training, especially increasing human resource capabilities. Keywords: integration, coffee, income, livestock, INTISARIPenelitian ini bertujuan untuk mengetahui pendapatan usahatani kopi dan ternak kambing serta kondisi pemberdayaan petani kopi sistem integrasi dengan ternak kambing. Penelitian dilakukan di Kecamatan Ronggur Nihuta, Kabupaten Samosir yang ditentukan secara sengaja. Populasi dalam penelitian ini adalah petani yang mengembangkan usahatani kopi secara terintegrasi dengan ternak kambing dan telah dibina Starbuck Farmer Support Centre sebanyak 87 KK dengan jumlah sampel 30 responden. Penelitian ini menggunakan data primer yang diperoleh melalui wawancara dengan responden dan data sekunder yang diperoleh dari sumber resmi seperti; dari Badan Pusat Statistik Kabupaten Samosir, dan sumber lainnya. Data dalam penelitian dianalisis secara deskiptif. Berdasarkan hasil penelitian disimpulkan; a) rata-rata pendapatan usahatani kopi sistem integrasi dengan ternak kambing Rp14.150.186,64; b) rata-rata pendapatan usaha ternak kambing denga system integrasi dengan komoditi kopi Rp4.685.738,13; c) Pemberdayaan yang dilakukan Starbuck Farmer Support Centre terhadap petani kopi system integrasi dengan ternak kambing, sangat berperan mendorong petani untuk mengikuti; pelatihan, penyuluhan, bimbingan teknis dan arahan terkait pengembangan usahatani kopi-ternak kambing secara terintegrasi. Berdasarkan hasil penelitian disarankan; a) agar petani mengoptimalkan pengelolaan usahatani tanaman kopi dengan ternak kambing secara terintegrasi, melalui pengingkatan pemahaman dan pengetahuan petani melalui penyuluhan, pelatihan, pengolahan limbah tanaman untuk pakan ternak dan pupuk; b) agar Starbuck Farmer Support Centre melakukan pembinaan secara berkelanjutan terutama peningkatan kemampuan sumber daya manusia (SDM). Kata kunci: integrasi, kopi, pendapatan, ternak.